2016
DOI: 10.1007/s00038-016-0882-0
|View full text |Cite
|
Sign up to set email alerts
|

Changes in knowledge, attitude and involvement of fathers in supporting exclusive breastfeeding: a community-based intervention study in a rural area of Vietnam

Abstract: The community-based education model should be maintained and considered for conducting further test in wider application to mobilize fathers in supporting EBF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 33 publications
2
27
1
1
Order By: Relevance
“…14 The results of this study indicated that there was no difference in husbands' average education, husbands' income, the number of children, and husbands' age with their knowledge, attitudes, and support because the results of the analysis showed that all p-values are <0.05. This was in line with the study of Buddhika Mahesh et al, 26 K. Abhinaya et al, 27 Laanterä et al, 28 Tran Huu Binch et al, 29 and Su-Ying Tsai. 30…”
Section: Resultssupporting
confidence: 88%
“…14 The results of this study indicated that there was no difference in husbands' average education, husbands' income, the number of children, and husbands' age with their knowledge, attitudes, and support because the results of the analysis showed that all p-values are <0.05. This was in line with the study of Buddhika Mahesh et al, 26 K. Abhinaya et al, 27 Laanterä et al, 28 Tran Huu Binch et al, 29 and Su-Ying Tsai. 30…”
Section: Resultssupporting
confidence: 88%
“…Bich & Cuong () found 81.2% of participants initiated breastfeeding within 1 hr after birth in the intervention group and 39.6% in the control group ( p < .001). Two studies found that the intervention groups including fathers increased breastfeeding initiation between 2.4 and 7 times (Bich & Cuong, ; Sahip & Turan, ). This was not supported in another study where there was no difference between intervention and control groups with respect to initiation of breastfeeding (Su & Ouyang, ).…”
Section: Resultsmentioning
confidence: 98%
“…WHO defined early breastfeeding initiation as infants put to the breast within 1 hr after birth, and exclusive breastfeeding as providing a child only breastmilk without solid or semi-solid supplements with the exception of oral rehydration solution, drops or syrups containing vitamins, minerals, and medicines. Bich & Cuong (2017) found 81.2% of participants initiated breastfeeding within 1 hr after birth in the intervention group and 39.6% in the control group (p < .001). Two studies found that the intervention groups including fathers increased breastfeeding initiation between 2.4 and 7 times (Bich & Cuong, 2017;Sahip & Turan, 2007).…”
Section: Breastfeeding Outcomesmentioning
confidence: 91%
See 1 more Smart Citation
“…In addition, the starting age of treatment, CD4 percentage, and opportunistic infection were found to significantly predict treatment outcome, implying the importance of clinical markers in the treatment response. Bich and Cuong (2016) completed a quasi-experimental, pre-test/post-test, non-equivalent control group design study, and concluded that breastfeeding, education materials, and counseling services yielded improvements in fathers' knowledge, attitude and involvement in supporting exclusive breastfeeding.…”
mentioning
confidence: 99%